Steroids from The Stem Bark of Dysoxylum nutans (Meliaceae) and Their Cytotoxic Effect Against MCF-7 Breast Cancer Cell Lines - Tri Mayanti; Nur Insani Amir; Dewa Gede Katja; Sofa Fajriah; Ahmad Darmawan; Unang Supratman; Khlaijah Awang; Yoshihito Shiono (Syarif Hidayatullah State Islamic University, 2020)
Three steroids, 3α-hydroxystigmast-5(6), 22-diene-7-one (1), stigmasterol (2) and 3-hydroxy-7β-methoxystigmast-5(6)-ene (3), were isolated from the stem bark of Dysoxylum nutans. The chemical structures were identified by spectroscopic data, which includes IR, 1D-NMR, 2D-NMR, and HR-TOFMS as well as by comparing previously reported spectral data. Compounds 1-3 were tested for cytotoxic effect against MCF-7 breast cancer cell lines and compound 1 showed the strongest cytotoxic activity with an IC50 value of 20.13 ± 0.06 μM.